„Bóg ukarał ją i oddał w ręce mężczyzny” - status prawny kobiet żydowskich w Izraelu na wybranych przykładach - Lubomski, Jakub (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article addresses the legal status of Jewish women in Israel after 1948. The analysis is based on selected examples that – presented in the socio-historical context – bring out the specific local character and incoherence concerning the observance of women rights. The explanations of marriage law and issues connected with divorce included herein are used to illustrate religious and historical regulations presently in force that overtly discriminate against women. The second part of the article takes on access to birth control, abortion and in vitro, which Israeli legislators perceive in progressive and liberal terms. Elucidation of the sources and foundations of Israeli law precedes the aforementioned analysis. This article was written in order to popularize the universal theme of women rights by using the example of Israel’s severely polarized reality. Furthermore, legal literature visibly lacks sources devoted to the subject of women’s rights in Israel. The reason for this state of affairs has also been laid out in the article
Keywords: Izrael; kobieta; małżeństwo; rozwód; aborcja; in vitro